California Bearing Ratio Properties of Peat Soil Stabilized with Crustacean Shell Waste (Chitosan) and Expanded Perlite (EP) Blends - Md Yusof, Zeety; Asri, Nurul Aida; Let, Mohamad Afiq; Leow Chee Sin; Pramono Rahardjo, Paulus (International Journal of Integrated Engineering, 2026)
Peat classified as soft soil, which leads to excessive settlement. This research is to characterize the physical properties of peat and to evaluate the enhancement in California Bearing Ratio (CBR) performance of peat stabilized using different proportions of chitosan-expanded perlite blends, with quantitative relationships between stabilizer concentration and CBR values under unsoaked conditions at 0-, 7-, 14-, and 28-day curing periods. Peat from Parit Nipah, Johor, were stabilized using chitosan percentages of 0.5%, 1.0%, 1.5%, and 2.0% in combination with a constant 10% expanded perlite. Both untreated and treated specimens were subsequently subjected to comprehensive physical and mechanical laboratory testing at the RECESS, UTHM. The results show peat highly organic (MC = 501%, Gs = 1.11, OC = 98.64%, FC = 21.07%, DOH = H7) with low compaction characteristics (MDD = 160 kg/m3, OMC = 142%) and very weak untreated CBR performance (16.10 lbf), while chitosan–expanded perlite significantly increased CBR loads (up to 56.89 lbf at 0 days and 46.75 lbf at 7 days in bottom layers), achieved optimum improvement at 14 days, but exhibited a strength reduction at 28 days, indicating a time-dependent stabilization. CBR values show that 1.5% chitosan (higher content mixture) increases unsoaked CBR values of peat within the range 2.9 - 3.5%, identified as providing an optimal dosage for enhancing, which found to be 0.5% by weight. Chitosan-expanded perlite treatment in ground improvement applications significantly enhances bearing capacity compared to untreated peat, thereby demonstrating a practical and sustainable construction solution for improving weak foundation soils.